The lighthouse on Moonglow Bay : a novel - Wilde, Lori (William Morrow, an imprint of HarperCollinsPublishers, 2022)
"It was an inheritance neither sister expected--a lighthouse in Moonglow Cove ... Harper and Flannery weren't exactly best friends ... And the sisters discover their grandmother's will has a stipulation: the two of them must live there, work out their issues ... Will they be able to come together and see their grandmother's wish come true? Or will these two sisters forever be estranged?"--